Software Product Line Engineering in Supply Chain Management Systems for Manufacturing Sector - Saviero, Jehian Norman; Raihan, Muhammad; Komarudin, Oman; Azurat, Ade (Ikatan Ahli Informatika Indonesia (IAII), 2025)
Manufacturing companies are industrial enterprises that process raw materials and implement Supply Chain Management (SCM). SCM encompasses three stages: material management, planning and control, and production. While these stages are common across manufacturing companies, the workflows and strategies employed vary based on the type of goods produced. For example, one company typically approaches process orders based on requests, whereas the other processes orders based on stock availability. To address these similarities and differences, a software product line engineering (SPLE) approach can be utilized to develop SCM systems. This approach has already been proven effective in other cases, such as developing various product specifications for our Crowdfunding Application (Amanah CS UI) partner. SPLE follows the principle of mass customization, analyzing the commonalities and variabilities of the SCM system to meet diverse company needs. This approach improves the cost optimization and time efficiency in developing various SCM specifications to fulfill the requirements of each company. The development of the SCM system in this study adopts a delta-oriented programming paradigm and Abstract Behavioral Specification programming language. Subsequently, a comparison was made between the development of the SCM system using the SPLE approach and the clone-and-own approach. The research results in an enhanced SCM system developed through the SPLE, establishing it as the primary solution to existing development issues: reusing shared components and adding new custom components. Additionally, it includes an analysis that compares the SPLE approach with the clone-and-own method.